Assessment of myocardial deformation with cardiac magnetic resonance strain imaging improves risk stratification in patients with dilated cardiomyopathy - Buß, Sebastian Johannes; Breuninger, Kristin; Lehrke, Stephanie; Voß, Andreas; Galuschky, Christian; Loßnitzer, Dirk; André, Florian; Ehlermann, Philipp; Franke, Jennifer; Taeger, Tobias; Frankenstein, Lutz; Steen, Henning; et al. (European heart journal - cardiovascular imaging, 2015)
AbstractAims. To investigate the prognostic impact of left-ventricular (LV) cardiac magnetic resonance (CMR) deformation imaging in patients with non-ischaemic